Comparação entre os fatores associados à resistência à insulina no final da infância e início da adolescência - Pani, Virgilia Oliveira (2017)
The objective of this study was to compare the risk factors associated with the development of insulin resistance (IR) at the end of childhood (8-9 years) and beginning of adolescence (10-14 years) in children and adolescents in the city of Vitória-ES. It is a cross-sectional study with 296 children and adolescents aged 8 to 14 years of public schools in Vitória / ES. Fasting plasma glucose, plasma insulin, total cholesterol and fractions (HDL and LDL), plasma triglycerides (TG), uric acid (AU), C-reactive protein and total leukocytes were determined. IR was assessed by calculating the HOMA-IR index. Measurements of weight, height, waist circumference (WC), perimeter of the neck (PN), perimeter of the hip (PH) and percentage of body fat (%BF) were obtained. Socioeconomic conditions, physical activity practice, eating habits, smoking and alcohol consumption were evaluated. We used the Shapiro Willk normality test, non-parametric tests and simple and multiple logistic regression models. The project was approved by the Human Research Ethics Committee of the Federal University of Espírito Santo (opinion n°. 1.565.490). Of the participants, 54.4% were female and 53.7% were adolescents. The female sex and the adolescence presented greater chances of inadequacy of insulin and IR. Adolescence presented a greater chance of inadequate number of meals, tablet or cellular use, screen time and alcohol consumption. All the anthropometric variables, time on the tablet or cell, time watching television (TV) and total screen time correlated positively with insulin and HOMA-IR. The IR group presented higher values of all the anthropometric variables and most of the biochemical and lifestyle variables, as well as the higher HOMA-IR quartile. Individuals who presented overweight, inadequate WC, PH, PN, Waist / Stature Relationship, excess body fat, inadequate glucose, HDL, TG, TG/HDL ratio, uric acid, insulin, metabolic syndrome, TV, longer screen time, greater family availability of sugar and individuals whose father does not work out were more likely to have IR. In the final model, the excess body fat, the TV watching time above 2h/day and the father did not work out were related to IR in the total sample. In childhood, the TG/HDL ratio ≥p90, AU ≥p90 and the TV watching time was higher than 2h/day and in adolescence the excess body fat, the TV watching time was higher than 2h/day and the family received a government appeal. It was concluded that the risk factors related to IR after 12 adjustments demonstrated different behaviors in the phases evaluated. In this way, it is extremely important to consider the phases separately when evaluating them.